Die Rolle der Schulsprachenpolitik bei der Normalisierung der llengua pròpia in Katalonien und der Region Valencia seit Beginn der Transición - Ina Kühne (Linguistik Online, 2022)
Catalonia and the Valencian Country are characterized by a very special sociolinguistic situation, which consists in the coexistence of the Castilian language as the official language of the Spanish state and the regional languages as co-official languages in the respective Autonomous communities. This constellation holds the potential for political tension, since in the past ‒ but still today ‒ it lead/leads to linguistic conflicts, whose origins lie in the political history of Spain, during which the regional languages time and time again were subject to repressions and prohibitions, that came to a head during the dictatorship of Francisco Franco. Since the beginning of the Spanish transition to democracy it was possible to work towards a resolution of the linguistic conflicts by means of legal norms and a corresponding language legislation. Especially the language teaching policy is an important area of language policy, since it has a long-lasting influence on the language skills of the citizens. The present article gives a detailed description of the measures taken in Catalonia and the Valencian Country concerning the language teaching policies since the beginning of the Spanish transition to democracy. Furthermore, it analyzes, in what way the language skills of the citizens of the Autonomous communities of Catalonia and Valencia have been improved through the applied language teaching policies and finally offers a comparison between the two Regions in this respect. The analysis is based on statistical surveys realized by the Institut d’Estadística de Catalunya (IDESCAT) and the Generalitat Valenciana.